Synthesis of Novel Glycosyl Carbamo(dithioperoxo)thioate Derivatives - Gucchait, Arin; Ghosh, Sritin; Misra, Anup Kumar (Synthesis, 2020)
A straightforward, one-pot reaction procedure is developed for the synthesis of novel glycosylated carbamo(dithioperoxo)thioate derivatives via N-iodosuccinimide (NIS)-mediated condensation of different glycosyl thiols, carbon disulfide (CS2) and various amines. The reactions occur rapidly and afford good to high yields of the corresponding products.
Keywords: carbohydrates; carbamo(dithioperoxo)thioates; one-pot; dithiocarbamates; glycomimetics